"On the Street, the Only Person You Gotta Bow Down to Is Yourself": Masculinity, Homelessness, and Incarceration. (23rd February 2022) - Umamaheswar, Janani
Abstract: Despite the well-established link between homelessness and incarceration, very little qualitative research has focused on the social processes that underlie this nexus. In this article, I draw on 19 in-depth interviews with incarcerated men who reported pre-prison housing instability, supplemented with 5 interviews with formerly-incarcerated men experiencing homelessness, to explore the gendered nature of the homelessness-incarceration nexus. I propose the concept of "liberative instability"—defined as an unfettered lifestyle characterized by double-edged freedom and independence—to explore the changing meaning of homelessness in men's narratives of their life course. Additionally, I explore how themes of masculinity and liberative instability are embedded in men's narratives of freedom and confinement as they reflect on their experiences with homelessness and incarceration. These findings animate existing quantitative research by highlighting that the homelessness-incarceration nexus cannot be understood fully or disrupted without considering the significance of age-graded cultural scripts regarding masculinity.